The Effect of Managerial Ownership, Institutional Ownership, and Financial Performance on Carbon Disclouser Emissions in the Metal and Mineral Sub-sector Listed on the Indonesia Stock Exchange in 2021-2024 - Dzikri Athar; Lilis Lasmini; Novy Triyanthy Noegraha (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the influence of managerial ownership, institutional ownership, and financial performance on carbon emission disclosure in metal and mineral sub-sector companies listed on the Indonesia Stock Exchange during 2021-2024. The method used is a quantitative approach with secondary data and purposive sampling technique, resulting in 100 observations from 25 companies. The results indicate that managerial ownership influences carbon emission disclosure, while institutional ownership has a significant negative effect and financial performance has an insignificant positive effect on carbon emission disclosure. due to differences in orientation in decision making